The comprehensive healthcare policy and education in the areas of health - Jorge Andrés Rubio-Romero (Federación Colombiana de Obstetricia y Ginecología, 2016)
The study conducted by Bayron Manuel Ruiz-Hoyos and Dora Cardona-Rivas at Universidad del Quindío provides the information on how a research-action approach was used to define the competencies in the basic areas of training of a medical professional, and the process for their evaluation. The clinical areas are the second component of medical training in health sciences schools and have their own challenges when they involve, according to the Tuning model for Latin America, cross-cutting (communication, ethics, professionalism, management, research, education) and professional (clinical care and specific knowledge) competencies (1, 2) that are required to incorporate the competencies proposed by the Ministry of Health and Social Protection in its Comprehensive Healthcare Policy (3).